2018
DOI: 10.1177/1938965518762837
|View full text |Cite
|
Sign up to set email alerts
|

Natural Occupancy Shifts in Hotel Markets

Abstract: The natural occupancy rate underpins room price adjustment models for hotel market evaluations; however, models that assume that this rate is time invariant and everywhere constant may introduce error when forecasting future real room rates and benchmarking market strength. We use monthly STR room rate and occupancy data for five large U.S. metropolitan hotel markets to estimate natural occupancy differences in time and across markets. The notion of a time-varying natural occupancy aligns with changing market … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…deRoos estimated the natural occupancy level on a nationwide basis to be 62.9%, with individual markets showing natural occupancy levels ranging from 56.4% to 75.9%. Gallagher and Corgel (2018) subsequently identified that natural occupancy rates are time varying and regime varying and that the natural occupancy rates are higher for higher priced hotels. Their research, which included monthly occupancy and ADR observations from 1988 through 2017, suggested that natural occupancy rates range from 60% to 77% depending on the city, lodging subgroup, and whether the market is in a normal or recessionary environment.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…deRoos estimated the natural occupancy level on a nationwide basis to be 62.9%, with individual markets showing natural occupancy levels ranging from 56.4% to 75.9%. Gallagher and Corgel (2018) subsequently identified that natural occupancy rates are time varying and regime varying and that the natural occupancy rates are higher for higher priced hotels. Their research, which included monthly occupancy and ADR observations from 1988 through 2017, suggested that natural occupancy rates range from 60% to 77% depending on the city, lodging subgroup, and whether the market is in a normal or recessionary environment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The fixed and perishable nature of room inventory coupled with widely fluctuating demand patterns compel hotels to continuously adjust their prices and their sales and marketing tactics (Kimes, 1989), making the process of managing revenues more complex (Erdem & Jiang, 2016;Kimes, 2015). Understanding market dynamics is critical not only for investors making decisions about where to build new hotels (deRoos, 1999) but also for managers and revenue managers tasked with optimizing revenues and managing inventory for their properties (Gallagher & Corgel, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations